Nanometric Pb1-xLaxTiO3 (x=0, 0.13 and 0.27) powders obtained by the polymeric precursor method - Rangel, J. H. G.; Goncalves, P. R. G.; Oliveira, M. M.; Bernardi, M. I. B.; Longo, Elson [UNESP]; Soledade, L. E. B.; Santos, I. M. G.; Souza, A. G. (Pergamon-Elsevier B.V. Ltd, 2008)
PLT (Pb1-xLaxTiO3, in which x = 0, 0.13 and 0.27) powders were successfully synthesized using the polymeric precursor method, based on the Pechini method. The polymeric precursors were calcined at temperatures ranging from 350 to 500 degrees C for 4 h. X-ray diffraction (XRD) showed the evolution of the crystalline phase starting from the amorphous precursor. Thermogravimetric analyses (TG) and differential thermal analyses (DTA) of the powder precursors showed the influence of the pH on the elimination of organic material. PLT powders have a tendency to form agglomerates, what can be verified by comparing the values of the average particle sizes obtained by Brunauer-Emmett-Teller method, BET (D-BET) with the values of the average crystallite sizes obtained by XRD (D-XRD). (C) 2007 Elsevier Ltd. All fights reserved.
Keywords: ceramics; sol-gel chemistry; X-ray diffraction; thermogravimetric analysis (TGA)